Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmicb.2022.912652
|View full text |Cite
|
Sign up to set email alerts
|

The diversity in antimicrobial resistance of MDR Enterobacteriaceae among Chinese broiler and laying farms and two mcr-1 positive plasmids revealed their resistance-transmission risk

Abstract: This research aimed to investigate the microbial composition and diversity of antimicrobial resistance genes (ARGs) found in Chinese broiler and layer family poultry farms. We focused on the differences in resistance phenotypes and genotypes of multidrug-resistant Enterobacteriaceae (MDRE) isolated from the two farming environments and the existence and transmissibility of colistin resistance gene mcr-1. Metagenomic analysis showed that Firmicutes and Bacteroides were the dominant bacteria in broiler and layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Those findings were almost similar to this study as in this study 86.5% tetracycline-resistant strains were resistant to amoxycillin and ciprofloxacin [ 24 ]. The present research work demonstrated high frequency of resistance against tetracycline which was similar to another study, where high frequency of resistance was found not only against tetracycline but also against kanamycin, and pefloxacin [ 25 ]. In this study, we detected 82.9% resistance of the E. coli isolates against amoxycillin.…”
Section: Author's Point Of Viewssupporting
confidence: 90%
“…Those findings were almost similar to this study as in this study 86.5% tetracycline-resistant strains were resistant to amoxycillin and ciprofloxacin [ 24 ]. The present research work demonstrated high frequency of resistance against tetracycline which was similar to another study, where high frequency of resistance was found not only against tetracycline but also against kanamycin, and pefloxacin [ 25 ]. In this study, we detected 82.9% resistance of the E. coli isolates against amoxycillin.…”
Section: Author's Point Of Viewssupporting
confidence: 90%